2016
DOI: 10.1016/j.juro.2016.02.084
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Multiparametric Magnetic Resonance Imaging and Magnetic Resonance Imaging Targeted Biopsy in Risk Classification for Patients with Prostate Cancer on Active Surveillance

Abstract: Purpose To determine if multiparametric-MRI (mpMRI)-targeted biopsies may replace systematic biopsies to detect higher grade prostate cancer (Gleason score ≥ 7), and whether biopsy may be avoided based on mpMRI among men with Gleason 3+3 prostate cancer on active surveillance (AS). Materials and Methods We identified men with previously diagnosed Gleason score 3+3 prostate cancer on AS who underwent a mpMRI and a follow-up prostate biopsy. Suspicion for higher grade cancer was scored on a standardized 5-poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 23 publications
5
32
1
Order By: Relevance
“…We also did not have data on those who progressed to radical therapy prior to the first MRI scan. This is in fact true of most similar studies in the field , but must be borne in mind when interpreting these studies and ours. It does not detract from results related to follow‐up of patients who remained on active surveillance.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…We also did not have data on those who progressed to radical therapy prior to the first MRI scan. This is in fact true of most similar studies in the field , but must be borne in mind when interpreting these studies and ours. It does not detract from results related to follow‐up of patients who remained on active surveillance.…”
Section: Discussionsupporting
confidence: 72%
“…This is no longer the case when MRI risk stratification is taken into account. Other studies have shown that ~10% of men on active surveillance with no visible MRI lesion will be found to have upgrading if routine confirmatory biopsies are performed . In the present study, only 1.8% of patients with negative MRI were found to have upgrading on confirmatory biopsy.…”
Section: Discussioncontrasting
confidence: 66%
“…For instance, the upgrading of low‐grade tumors on MRI/US confirmation biopsy less than 6 months after random TRUS biopsy has been shown to occur in up to 35% of patients being considered for AS . In our study, 20 of 76 patients (26.3%) were found to have Gleason score upgrading on MRI/US fusion–guided biopsy.…”
Section: Discussionmentioning
confidence: 47%
“…Recabal et al. . confirmed these conclusions in their retrospective assessment of an institutionally maintained prospective dataset.…”
mentioning
confidence: 64%